ChemInform Abstract: A Greener Synthesis of 1, 8‐Dioxo‐octahydroxanthene Derivatives under Ultrasound. Issue 14 (20th March 2013) - Mulakayala, Naveen; Kumar, G. Pavan; Rambabu, D.; Aeluri, Madhu; Rao, M. V. Basaveswara; Pal, Manojit
Abstract CAN is described as efficient catalyst under the optimized conditions which avoid the use of harmful solvents such as the chlorinated ones.